Fabrication of Highly Stretchable Conductors via Morphological Control of Carbon Nanotube Network. Issue 21 (30th April 2013) - Lin, Lin; Liu, Siyao; Fu, Sirui; Zhang, Shuangmei; Deng, Hua; Fu, Qiang
Abstract Stretchable conductors, which can keep their excellent electrical conductivity while highly stretched, have been investigated extensively due to their wide range of applications in flexible and stretchable electronics, wearable displays, etc.; however, their preparation is often complicated and expensive. Herein, an efficient method to prepare high performance stretchable conductors through morphological control of conductive networks formed with carbon nanotubes (CNTs) in an elastomer matrix is reported. It is observed that an interface‐mediated method could be used to align randomly oriented filler during stretching and to induce buckling of CNTs during relaxation. Further morphological studies indicate the possible formation of a wavy CNT structure induced by cyclic pre‐straining. Subsequent thermal annealing is observed to collapse the oriented network and improve the local contacts between conductive networks. Through such a simple procedure, a conductivity of nearly 1000 S m−1 and a stretchability of 200% can be achieved for composites containing 20 wt% CNTs. CNTs are observed to buckle over a large area in polymer bulk, and the combination of pre‐straining and thermal annealing modifies the conductive network in the elastomer matrix. As a general method, this could be used for easy fabrication of high‐performance stretchable conductors for arbitrary‐shaped objects on a large scale.